x^{-2 }-1/x-1

## solving negative exponent simplification

Tutors, please sign in to answer this question.

# 1 Answer

x^{-2} - 1/x - 1 ______ given

= (1/x^{2}) - (1/x) - (1) ______ x^{-2} can be written as 1/x2 and use parentheses to separate each term

= (1/x^{2}) - (x/x^{2}) - (x^{2}/x^{2}) ______ LCD is x^{2}

= (1-x-x^{2})/(x^{2}) ______ combine terms into single fraction

= (-x^{2}-x+1)/(x^{2}) ______ rearrange terms in the numerator in descending order

= - (x^{2}+x-1)/(x^{2}) ______ factor -1 outside of the fraction [ANSWER]